Highly sensitive analytical method for herbicide clopyralid residue in cattle manure compost with ultraperformance liquid chromatography tandem mass spectrometry - Seike, Nobuyasu; Namiki, Sayuri; Watanabe, Eiki (Journal of Pesticide Science, 2019)
A micro liquid–liquid extraction has been applied to sample preparation in the current authorized method for clopyralid in compost. The method rendered matrix effects practically negligible during determination with ultraperformance liquid chromatography-electrospray ionization tandem mass spectrometry with an improved limit of quantification of 0.7 µg/kg dry weight. Moreover, it had good accuracy and reproducibility. Therefore, the method is proposed as a highly effective routine analytical technique for investigating the actual status of clopyralid residue in compost.